What drives engagement in the Clean Energy Ministerial?: An assessment of domestic-level factors - Tosun, Jale; Rinscheid, Adrian (Journal of European public policy, 2023)
This study concentrates on the Clean Energy Ministerial (CEM) as one of several high-level global forums on climate change governance. The CEM can be conceptualised as a ‘polycentric’ organisation in which its members collaborate on a wide range of issues concerning the clean energy transition. Can we identify a set of domestic-level variables that explain the member states’ participation across different CEM initiatives? And can we identify clusters of CEM initiatives for which the same set of domestic-level variables provide robust explanations? Theoretically, we concentrate on domestic factors and how these explain engagement patterns in high-level global forums. Our findings for 12 initiatives show that there is no single domestic factor that explains engagement levels equally well for all CEM initiatives. Our overarching finding is that the domestic determinants of engagement vary across the initiatives, suggesting that future research should attend more closely to their specific features.
Online veröffentlicht: 13 December 2021
Gesehen am 29.07.2024